General overview over the Third Sector in Romania today - Violeta Stanciu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The present paper aims to present the picture of the Third Sector in Romania, today and the way it relates to Law 219/2015 on the Social Economy. It was analyzed the current legislative text and the specific laws on establishing and functioning of the key organizations concerned. It has been made a documentary on statistical data provided by institutions such as The National Office of the Trade, The National Bank of Romania, the Institute of Social Economy. To analyze the degree of knowledge of the law by the potential beneficiaries and their opinion on the current legislative approach, there were conducted semi-structured interviews and questionnaires were administered by phone and e-mail. Responders were chosen from the representatives of NGOs and cooperative federal bodies. It was found that the Third Sector has experienced a steady development in recent years but not all the organizations listed by law can become or are interested in becoming Social Enterprises. Due to legislative inconsistencies, bureaucracy and the lack of fiscal or financial incentives, the degree of interest in obtaining the status of a social enterprise is currently low. It remains to be seen whether future developments draw attention to Law 219/2015 and to related legislative approaches. But, regardless of this, the return to the basic principles of the social economy in the XIX-th century of which the connection between the economic activity and the social and moral values to be respected and the way to make efficient the own economic activity even without governmental or European financial assistance may have a decisive role for the development of the Social Economy sector in Romania and in Europe in general.
Keywords: L31; A13; D71; 330; Social Economy; Social Enterprise; Community Economy; Cooperative; The Third Sector